Five on a hike together - Blyton, Enid (Hodder Children's London, 2001)
The first night of the Five's hike, Dick and Anne get lost in the rain. Dick hears a mysterious whispered message, which sends them on the trail to Two-Trees, by Gloomy Water, and what IS going on there?